The Role of Religious Moderation in Improving Social Harmony in Multicultural Society - Fikri, M. Ahsanul; Prakosa, Prakosa; Tara, Alifia; Zeny , Rahmawati (Khidmatuna: Jurnal Pengabdian Masyarakat, 2024)
This community service is carried out with the aim of raising public awareness of the importance of religious moderation in creating and improving social harmony in a multicultural society. Religious moderation refers to an approach that emphasizes balance, tolerance, and respect between individuals with different beliefs. The purpose of this community service is to educate and provide an understanding of the role of religious moderation in building social harmony and reducing conflict in a society with diverse backgrounds. The results of the community service activities show that religious moderation plays an important role in preventing inter-religious conflict, supporting an inclusive society, and preventing religious radicalization. Religious moderation also contributes to increasing the ability for dialogue and cooperation between communities of different beliefs. In addition, activities such as religious moderation workshops and eco-enzyme training held by UIN Walisongo Semarang strengthen social relations, promote moderation values, and teach new skills that are beneficial to the environment. Religious moderation is able to create a harmonious and inclusive society by respecting differences, and providing significant benefits through collaboration in social and environmental activities.